2010
DOI: 10.1128/aac.00801-09
|View full text |Cite
|
Sign up to set email alerts
|

Fitness Costs and Stability of a High-Level Ciprofloxacin Resistance Phenotype in Salmonella enterica Serotype Enteritidis: Reduced Infectivity Associated with Decreased Expression of Salmonella Pathogenicity Island 1 Genes

Abstract: The fitness costs associated with high-level fluoroquinolone resistance were examined for phenotypically and genotypically characterized ciprofloxacin-resistant Salmonella enterica serotype Enteritidis mutants (104-cip and 5408-cip; MIC, >32 g/ml). The stability of the fluoroquinolone resistance phenotype in both mutants was investigated to assess whether clones with better fitness could emerge in the absence of antibiotic selective pressure. Mutants 104-cip and 5408-cip displayed altered morphology on agar an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
56
1
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(64 citation statements)
references
References 47 publications
5
56
1
2
Order By: Relevance
“…In contrast, the high level of resistance to ciprofloxacin in in vitro-derived mutants of S. enterica is associated with fitness costs. In the absence of evidence of compensatory evolution, such fitness costs may account for the lack of emergence and spread (to date) of highly resistant S. enterica clones via the farm-to-fork route (120). Moreover, quinolone-resistant Salmonella spp.…”
Section: Resistance To Fluoroquinolones and Effect On Virulencementioning
confidence: 99%
“…In contrast, the high level of resistance to ciprofloxacin in in vitro-derived mutants of S. enterica is associated with fitness costs. In the absence of evidence of compensatory evolution, such fitness costs may account for the lack of emergence and spread (to date) of highly resistant S. enterica clones via the farm-to-fork route (120). Moreover, quinolone-resistant Salmonella spp.…”
Section: Resistance To Fluoroquinolones and Effect On Virulencementioning
confidence: 99%
“…Recently, however, a relationship between acquisition of high levels of fluoroquinolone resistance and decreased cell invasion ability has been reported, and this may explain why, in general terms, a high prevalence of fluoroquinolone-resistant S. enterica strains remains rare among clinical isolates. These resistant bacteria show an impaired growth rate which may appear as a consequence of the acquisition of fluoroquinolone resistance and compromise the expression of the invasion genes (50)(51)(52). In view of these results, azithromycin and aztreonam are alternative agents that may be useful for patients with multiple allergies or for organisms with unusual resistance patterns (29).…”
Section: Antimicrobial Treatment and Resistancementioning
confidence: 99%
“…Nevertheless, results from previous studies suggest that high-level CIP resistance mechanisms in Salmonella lead to restrictive conditions of itness costs and minimizing the emergence and spread of highly resistant clones in the absence of drug selection pressure [101,102]. As demonstrated in previous study [103], high-level CIP-resistant S. Enteritidis in vitro derived mutants in the absence of antibiotic selective pressure result in compensatory evolution favoring a reversion back to a more sensitive phenotype associated with lesser itness costs, rather than the compensatory mutations that would restore resistance. However, under in vivo conditions, a previous study has found that chromosomal mutations of S. Typhimurium that confer resistance to NAL, streptomycin, or rifampicin decrease growth rate and ability to colonize in mice rather than a reversion to the susceptible phenotype and restore virulence [104].…”
Section: The Itness Costsmentioning
confidence: 61%